HUBUNGAN TINGKAT PENGETAHUAN IBU DAN ASUPAN GIZI PMT PENYULUHAN DENGAN STATUS GIZI BALITA DI POSYANDU WILAYAH KERJA PUSKESMAS KARANGASEM II - Kadek Ayu Mega Widawati; I Made Suarjana; A.A.Gde Raka Kayanaya (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
Nutritional problems are still a health problem especially in toddler groups. Maternal knowledge is one of the factors affecting nutritional status In addition to the level of consumption. Fulfillment of one of the consumption levels can be fulfilled through the provision of PMT counseling. Research objectives to know the relationship level of mothers knowledge and nutritional intake of PMT counseling with nutritional status. The research was done to the toddler in the working area of Public Health Center Karangasem II, Karangasem District in March 2020. Samples amounted to 100 people. The nutritional Status of toddlers is measured by weighing weight and measuring height and comparing to the standard. Knowledge of mothers is measured by way of interviews with questionnaire guidance. PMT extension is obtained by interviews. Respondents in this study included toddler mothers. Data analysis using Pearson Correlation test and Chi Square.The results showed that most of the toddlers with good nutritional status of 87 people (87.0%) and 13 people (13.0%) Less nutrition. The level of knowledge about PMT is mostly 61 people with sufficient categories of 61%, energy intake level data PMT counseling with good category is 94%, protein intake level data PMT counseling with good category of 88%, data based on the number of PMT counseling most of the categories obtained quite varied that is 50%, and the category data type PMT extension obtained PMT type local counseling is 80%. Statistical test results using Pearson and Chi Square correlates, obtained all the results of P-value α = 0.05 which means there is no link between maternal level of knowledge, energy intake, protein, PMT number of counseling and PMT category of counseling with nutritional status. Keywords: knowledge level, PMT extension, nutritional status